FTA Highlight No.16 – Capacity Development - Wardell, D.A.; Meybeck, A.; Gitz, V.; Brady, M.A.; Cerruti, P.O.; Elias, M.; Duguma, L.A.; Hendre, P.; Jamnadass, Ramni; Kuria, A.; Louman, B.; Martius, C.; et al. (CGIAR Research Program on Forests, Trees and Agroforestry, 2022)
Capacity development is a key component of the pathways from research to impact, from upstream research to downstream outcomes. The term covers a typology of different activities to increase the capacities of various ranges of actors, in order to enable them to act for positive, sustained change. In the CGIAR Research Program on Forest, Trees and Agroforestry (FTA), capacity development was mainstreamed into the 25 operational priorities, and supported by a central coordination component. This FTA highlight summarizes the evolution of the concept of capacity development (CapDev), from the inception of the programme in 2011 through the FTA Capacity Needs Assessment (2018–2019) to the final FTA CapDev Plan of Action 2020–2021 (FTA 2020a). It provides an overview of the key activities undertaken in FTA and reflects on the relevant findings from related CGIAR and FTA evaluations.